Effect of substituting barley with corn or sorghum on rumen fermentation and post-ruminal starch digestion in lambs - Yahaghi, Mohammad (2011)
Locally grown barley is the primary dietary energy source for ruminant production in Iran. However, its production in recent years has declined due to increasing shortage of water in the barley cropping regions. In addition, barley ferments rapidly in the rumen and can lead to metabolic disorders. This thesis, consisted of three experiments, examined the suitability of replacing barley with corn or sorghum for lamb production in Iran. The first experiment evaluated the effects of partial substitution of barley with corn or sorghum on in situ dry matter and starch degradability followed by an in vivo feeding trial to examine intake and performance in finishing Iranian Baluchi lambs. In the in situ experiment, individual grains include ground barley, corn (C) and sorghum (S) and their mixtures in various combinations; 70 barley: 30 corn (LC), 70 barley: 30 sorghum (LS), 30 barley: 70 corn (HC) or 70 sorghum (HS) were incubated in nylon bags in the of fistulated Holstein steers. Results of this experiment showed that ruminal degradability of barley was higher than corn and sorghum, and further suggested that in order to effectively decrease ruminal degradability of barley with corn or sorghum, the substitution rate needs to be about 70%. In the follow-up in vivo trial, thirty Iranian Baluchi male lambs at approximately 65 days old (32 ± 3.2 Kg) were allocated into individual pens and fed five experimental diets. The control diet contained 56% ground barley (B) as source of energy in the concentrate, and in the treatment diets, barley was substituted by ground corn and sorghum in either 30% or 70% to give low corn (LC), high corn (HC), low sorghum (LS) and high sorghum (HS) diets, respectively. HC and HS diets significantly improved ruminal pH with lambs in HS and HC diets recorded 35% and 15% higher average daily gain (ADG), respectively, than lambs in the control diet. Results of this study indicated that in order to enhance animal performance, the substitution rate of barley by corn or sorghum should be about 70% and in addition, substituting barley with sorghum was better than with corn. The second experiment (Chapter 4) was designed to quantify the rate of ruminal DM, starch and N outflows and their post-ruminal digestibility when barley in the concentrate was substituted at 50% or 100% with sorghum. Eighteen male lambs (65 days of age and 31±1.9 kg live weight) were randomly allocated into three dietary treatments. The diets were similar to those of the previous experiment which barley was the main energy source in the concentrate of control diet while the others were 50% barley: 50% sorghum (BS) and 100% sorghum (S). Lambs in high barley (B) diet had higher total volatile fatty acids (VFA) production, thus lowest ruminal pH (5.9). Majority of the post-ruminal DM, starch and N were digested in the distal-duodenum followed by the anterior jejunum. Although lambs fed high sorghum (S) diet recorded higher outflow rates (g/d) of starch into the small intestine, because of its low digestibility, the ruminal starch outflow was poorly digested, leaving significant quantity been fermented in the large intestine or as waste excreted in the faeces. On the other hand, ruminal fermentation of starch and N in lambs fed barley-sorghum (BS) diet was well synchronized, leading to significant (P<0.05) improvement in growth rate of the lambs. The final study (Chapter 5) was designed to examine whether extrusion treatment would enhance the digestibility of sorghum starch to allow for 100% substitution of barley by sorghum in lamb diet. Based on results of in situ degradation rate and post-ruminal digestion parameters, extrusion using 150°C and 55 bar pressure was found to be most effective for sorghum. In a follow-up experiment, eighteen male Iranian Baluchi lambs randomly allocated into three dietary treatments which include 100% barley (B) in the concentrate as control, 50% barley: 50% extruded sorghum (BSE) and 100% extruded sorghum (SE). Because of the lower apparent ruminal degradability of the starch, higher abomasal flow of starch and N was recorded for lambs in the 100% extruded sorghum (SE) diet. In addition, higher starch and N was digested in the SE compared to B and BSE diets. The higher quantity of starch digested and absorbed mostly as glucose in the SE diet group was reflected by the corresponding higher glucose concentration in portal vein of lambs fed SE diet. Lambs in SE diet also recorded higher microbial N supply, ADG and more efficient feed conversion ratio compared to lambs in the B or BSE treatments.